SIGNS AND CODES IN A MILD BILLBOARD ADVERTISEMENT - SANTHI, ADITYA FATMALA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Everyday when we go somewhere, we often see A Mild advertisements onbillboards on the side of street with imaginative picture and few lines of messages.Advertisement gives various information which aims at persuading the audiencesand also ensuring the reader or listener that their products are so good, so peoplewill be interested to buy the product. The writer is aimed to find out: (1) the kindsof signs found in A Mild billboard ads and (2) the kinds of codes found in A Mildbillboard ads.This study uses qualitative approach in terms of content analysis. Since thefocus of the study is on the signs and codes in the advertisements, the theories ofcode proposed by Barthes(1974) and Chandler ( 2002) are  used. The writerchooses four versions of A Mild Billboard advertisement.This study reveals that the iconic signs are mostly used in these ads. Thewriter sees that visual elements in the form of icons are mostly used. The writersees that theories are not only found in the form of visual elements of A Mildadvertisement which are divided into icon, index, and symbol but also in theverbal elements of A Mild advertisements in the form of symbol as thevisualization of verbal language in the form of words, phrases, sentences ordialogue. Based on the writer’s analysis to these A Mild advertisements, the codesusually use more iconic signs since the number of iconic signs used in the A Mildadvertisements is fewer than others.Finally, the next researchers can analyze how the codes are valuable inrelating signs and meaning in other visual communication forms and they cancompare their analysis to the result of this research. Keywords: sign, code, icon, index, A Mild billboard advertisement